Internal Consistency of the Customized Employment Discovery Fidelity Scale: A Preliminary Study. (April 2023) - Riesen, Tim; Hall, Stephen; Keeton, Beth; Snyder, Aubrey
The Discovery Fidelity Scale (DFS) is a 15-item instrument used to determine fidelity to discovery best practices at the systems and services level. Fidelity scale development is typically guided by an iterative, three-part process that includes identifying and specifying the fidelity structure and content, measuring and confirming the content, and assessing the internal consistency and reliability of the scale. This study is the initiation of the third step of the fidelity process to determine if items on the DFS accurately and reliably measure the discovery construct (internal consistency). The study also examined outcomes for individuals engaged in the discovery process. The results of the study suggest that (a) both the systems and services components appear to measure their respective constructs and (b) the overall discovery construct appears to have acceptable internal consistency.